KONSEKUENSI YURIDIS PENYIMPANGAN KEWENANGAN INTERSEPSI OLEH PENEGAK HUKUM - Wahyudi, Slamet Tri (Jurnal Hukum dan Peradilan, 2012)
Interception is an act that violates human rights is therefore authorized the interception can only be done by law enforcement officers. In reality interception authority by police to deviate from the provisions that have been mandated by law. This research is a normative legal normative juridical approach. The data collected is secondary data were analyzed using qualitative methods juridical analysis. Based on this study it can be concluded that the juridical consequences of the actions of police conduct authority lapses in implementing the interception an act that is against the law and may be subject to criminal sanctions, it is based on a systematic interpretation of Article 31 paragraph (3), the law enforcement officers who perform deviation authority interception the position equivalent to ordinary people who do the interception as stipulated in Article 31 paragraph (1). So the police action could be sanctioned as provided for in Article 31, paragraph 1 in conjunction with Article 47 of Law ITE. Keywords: Deviation, authorized, Interception, Law enforcement